Sisters in arms : a novel of the daring Black women who served during World War II - Alderson, Kaia (William Morrow, an imprint of HarperCollins Publishers, 2021)
"Grace Steele and Eliza Jones may be from completely different backgrounds, but when it comes to the army, specifically the Women's Army Auxiliary Corps (WAAC), they are both starting from the same level. Not only will they be among the first class of female officers the army has even seen, they are also the first Black women allowed to serve. As these courageous women help to form the 6888th Central Postal Directory Battalion, they are dealing with more than just army bureaucracy--everyone is determined to see this experiment fail. For two northern women, learning to navigate their way through the segregated army may be tougher than boot camp. Grace and Eliza know that there is no room for error; they must be more perfect than everyone else. When they finally make it overseas, to England and then France, Grace and Eliza will at last be able to do their parts for the country they love, whatever the risk to themselves. Based on the true story of the 6888th Postal Battalion (the Six Triple Eight), Sisters in Arms explores the untold story of what life was like for the only all-Black, female U.S. battalion to be deployed overseas during World War II." --